Comparación cuantitativa y cualitativa del pavimento flexible con el rígido en la carretera Cuñumbuqui – Estero, provincia de Lamas, región San Martín - Layza Mendiola, Ricardo Martín (2013)
This thesis has been developed in the Academic Professional School of Civil Engineering, Faculty of Civil Engineering and Architecture at the National University of San Martin - Tarapoto purposes degree in Civil Engineering, with the operating point of the road section Cuñumbuqui - Estero province of Lamas, San Martin Region. The research was conducted in order to establish a qualitative and quantitative comparison between the use of rigid pavement and flexible pavement, since they must be chosen by a technical, economical and viable solution to define the paving of this road that requires urgent attention to be in traffic conditions, actively participating in the solution of the existing road problems in rural areas of the province of Lamas; the current state of the roads is having problems walkability, generating costs of transporting the products from the countryside to the city are high, so the economy of farmers affected and therefore the quality of life of the same; It is a rough road, causes delays and inconvenience in moving the country to the city and vice versa, finding that although it is certain farm products are taken to the city, it is also true that the farmer has to return the field leading products for subsistence, as well as those required for agriculture. So it has participated in the formulation of the project in question to achieve a local road pavimentado.Como achievements or results we obtained indicate that the rigid pavement is the most economical, the result of which shows its best performance considering factors both technical and economic. As connoisseurs of bad state in which is currently the road under study and aware of our social responsibility as an integral part of the National University of San Martin, we are helping to solve this problem, proposing an alternative solution in improving the said communication path, thereby benefiting will be the same user communities, noting that this project is of vital importance as a purely agricultural area. In this way it contributes to economic and social development of the beneficiary villages, because the standard of living of its population increases, contributing to the development of our country, besides getting our knowledge is put into practice and develop our professional sense the race.